Encyclopedia of machine learning - Sammut, Claude; Webb, Geoffrey I. (Springer, 2011)
This comprehensive encyclopedia, in A-Z format, provides easy access to relevant information for those seeking entry into any aspect within the broad field of Machine Learning. Most of the entries in this preeminent work include useful literature references.